Structural evolution of FeH4 under high pressure. Issue 21 (22nd February 2017) - Li, Fei; Wang, Dashuai; Du, Henan; Zhou, Dan; Ma, Yanming; Liu, Yanhui
Abstract : Here, we systematically investigated global energetically stable structures of FeH4 in the pressure range of 80–400 GPa using a first-principles structural search. Abstract : The solid inner core of Earth is mainly composed of an iron-rich alloy with nickel and some lighter elements like hydrogen, carbon, and oxygen, but the exact composition and chemical reactions are still elusive. Hydrogen has been proposed as the main element responsible for the density deficit observed in the Earth's inner core. Moreover, the solubility of hydrogen in iron increases considerably with increasing pressure. Here, we systematically investigated global energetically stable structures of FeH4 in the pressure range of 80–400 GPa using a first-principles structural search. A transition from an insulated α-phase to a metallic β-phase and then to a semi-conductive γ-phase was predicted. Interestingly, we find a superconducting state in the β-phase with a transition temperature of 1.70 K at 109.12 GPa. The results are useful for investigating the stable phases and equation of state in the Fe–H system, which are relevant to the Earth's core.